MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) DALAM MENINGKATKAN KEMAMPUAN BERPIKIR KREATIF DAN RASA INGIN TAHU PESERTA DIDIK DALAM PEMBELAJARAN PAI - Anisatul Mufidah Anisatul; Muhammad Rifa’I Subhi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
In the PAI learning process, a high level of curiosity is needed to support successful learning. Apart from that, creative thinking skills are also needed to solve problems. An attitude of curiosity and creative thinking abilities can be developed in the application of a learning model. This research aims to examine whether the learning modelproblem-based learning can increase students' curiosity and creative thinking abilities in PAI learning. This research uses a qualitative approach with methodsthe study of literature. In this research, researchers look for data or information related to the learning modelproblem-based learning, creative thinking abilities, and students' curiosity. The results of this research concluded that the use of learning modelsproblem-based learning can increase students' curiosity and creative thinking abilities in PAI learning. Apart from that, researchers also concluded several indicators to measure students' curiosity in learning with modelsproblem-based learning, including: (1) exploring related material, (2) having a desire to know more deeply, (3) trying to dig up information from other sources, and (4) asking questions both to teachers and friends.